Identifikasi Budaya Rambu Solo’ dalam Menunjang Pariwisata di Kabupaten Toraja Utara - Langi, Reka Tanduk; Maliangkay, Denny; Rifani, Irfan; Karwur, Hermon Maurits; Putri, Anindya Puspita (Jurusan Pendidikan Geografi Universitas Negeri Manado, 2024)
The Rambu Solo' ceremony, a traditional funeral rite of the Toraja people in North Toraja Regency, holds significant cultural and tourism potential. This study aims to identify the cultural aspects of Rambu Solo' and analyze its role in supporting tourism. Employing a qualitative descriptive approach, the research was conducted in Salu Sopai Village, Sopai District, North Toraja Regency, involving local community members, government representatives, and tourists as informants. Data were collected through observation, interviews, and documentation. Findings reveal that Rambu Solo' integrates complex cultural values, such as social hierarchy and community participation, into a unique tourism attraction. Using the 5A approach; attraction, accessibility, amenities, accommodation, and activities the study highlights both the strengths and challenges of leveraging Rambu Solo' for sustainable tourism. Recommendations include infrastructure improvement, cultural preservation, and enhanced promotion to attract national and international visitors. The findings underline the importance of community involvement and cultural heritage in fostering tourism while respecting traditional values.